Level of Independence and the Mental Status of the Visually Challenged High School Students in Chennai - Shanthi Edward; Vijaykumar Edward; Kritika V (Medsci Publications, 2022)
Background: The purpose of this study is to measure the number of visually impaired students who are capable of doing and managing their own work and also to evaluate their state of mind due to their impairment. The study is also to bring awareness about the rehabilitation centres and special training on mobility for the children. Objective: To find out the level of independence and the mental status of visually challenged students. Methods: This is a descriptive cross-sectional study. Sixty visually impaired students were included in the study by random sampling method. Male students from class 9th to 12th standard were evaluated. Data relevant to the study are gathered by interview schedule method and questionnaire was designed for the study beforehand. Result: It is evident from the current study that 83.3% of the impaired have not been trained to walk independently. Almost 78.3% of the students are not even aware of the rehabilitation centres. However, about 98.3% of students are independent in grooming and washing & also taking care of their personal work. As per the survey, only 26.6 % of students are feeling isolated, whereas, the balance 73.4% students feel very comfortable while dealing with sighted students. About 96.6% feel very happy and satisfied as they get enough support from their parents.